Building the European capacity in operational oceanography : proceedings of the Third International Conference on EuroGOOS : 3-6 December, 2002, Athens, Greece - Dahlin, H. (Elsevier oceanography series, 2003)
This proceedings 3rd EuroGOOS Conference on Building the European Capacity in Operational Oceanography is volume 69 in the Elsevier Oceanography Series. The topics of the proceedings cover: Regional Systems I, Remote Sensing Systems, Numerical Modelling and Data Assimilation, Next Generation Systems, EC Operational Forecasting Workshop: Reports on EC Operational Forecasting, In-Situ Monitoring, Waves Monitoring and ForecastingUser Perspectives, EuroGOOS Task Teams, Regional Systems 2, Coastal Systems, Data - Products - Users, and GMES Marine Forum.